Effect of Chronic Administration of Hydromethanol Leaf Extract of Helianthus annuus on Erythrocytic Profile in Normal Rats - O. Onoja, Samuel; C. Udem, Samuel; O. Anaga, Aruh (Journal of Nutritional Therapeutics, 2017)
Effect of chronic administration of hydromethanol leaf extract of Helianthus annuus on erythrocytic profile in normal rat was investigated. The extract was prepared using cold maceration method and concentrated at 40˚C. It was incorporated in feed at 2.5, 5 and 10 mg per 100 g feed. Albino rats were randomly assigned to 4 (A – D) groups of 14 rats each. Group A received standard feed while groups B – D received feed incorporated with H. annuus at 2.5, 5 and 10 mg/10 g feed, respectively. They were fed 10% of their body weight daily for 90 consecutive days. Blood samples were collected via retroorbital venous plexus from four rats selected at random from each group without replacement on day 30, 60 and 90 for the determination of erythrocytic profile. There was no significant (p > 0.05) change on the erythrocytic profile of the various groups on day 30 and 60 while the packed cell volume and hemoglobin concentration of H. annuus treated groups were significantly (p < 0.05) lower than group A rats on day 90. This study suggests that the chronic use of Helianthus annuus for up to 90 days in rat may lead to anemia and should be avoided.